Pengaruh Waktu dan Tekanan Gesek terhadap Kekuatan Tarik Sambungan Paduan Aluminium dan Baja Karbon pada Pengelasan Gesek Continuous Drive - Pah, Jack Carol Adolf; Irawan, Yudy Surya; Suprapto, Wahyono (Jurnal Rekayasa Mesin, 2018)
The objective of this research was to investigate the effect of friction time and friction pressure on the tensile strength of the joining of two dissimilar materials, aluminum alloy AA6061 and carbon steel, with continuous drive friction welding process. Variations of friction times of 5 seconds, 7 seconds, 9 seconds, and 11 seconds, at each variation of friction pressures of 24 MPa, 32 MPa, and 40 MPa. Controlled variables in this friction welding process were rotational speed of 1600 rpm, upset pressure of 79 MPa which was applied for 60 seconds and diameter of friction surface of specimens which were 15 mm. The resulting strength of the bonding were than evaluated on the basis of tensile strength. Observations of temperature change during the welding process, the distribution of Vickers hardness values around the bonds area, and micro photographs, were used as support to the analysis. The results showed that the longer friction time was applied, the higher tensile strength of the bonds would be, until it began to decrease after a certain maximum value of the tensile strength had been reached. Increased of the tensile strength of the bonding did not occur linearly due to the variation of friction pressure at 9 seconds and 11 seconds of friction time. At 5 seconds and 7 seconds of friction time, increase of friction pressure caused a linear increase of tensile strength. Higher temperatures in the welding process increased the thickness of brittle layer at the bonds boundary. The increase of the brittle layer thickness causes decrease of the tensile strength of the bonds.